1984
DOI: 10.1007/bf01032602
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline tumorigenicity in swiss strain mice on normal and vitamin B deficient diet

Abstract: Arecoline, a major alkaloid present in betel nut, was administered daily by gavage feeding to Swiss male and female mice at a dose of 1 mg/day/mouse five times a week, either alone or in combination with KNO3 or KNO3 + lime. Swiss mice of both sexes kept on a vitamin B complex-deficient diet were tested in a similar manner and compared with those receiving a normal diet. In the mice receiving a normal diet it was observed that arecoline induced tumors in 40% of males but failed to produce tumors in any of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The oral LD 50 value of arecoline in swiss albino male mice was 371 mg/kg [22]. A tumorigenicity study in swiss strain mice showed that arecoline treatment induced tumors in 43% of males at a dosage of 5 mg/animal/week (p.o) throughout their life-span [23]. Arecoline was positive in the mouse bone marrow micronucleus test at a dose of 2 mg/animal (i.p) administered twice [17].…”
Section: Discussionmentioning
confidence: 98%
“…The oral LD 50 value of arecoline in swiss albino male mice was 371 mg/kg [22]. A tumorigenicity study in swiss strain mice showed that arecoline treatment induced tumors in 43% of males at a dosage of 5 mg/animal/week (p.o) throughout their life-span [23]. Arecoline was positive in the mouse bone marrow micronucleus test at a dose of 2 mg/animal (i.p) administered twice [17].…”
Section: Discussionmentioning
confidence: 98%
“…However, arecoline has also been associated with the development of oral premalignant lesions and risk of oral cancer in many areas of Asia, the Pacific region, and in migrant communities in the United Kingdom, United States and South Africa where betel chewing is prevalent (Gupta and Warnakulasuriya, 2002; Sharan et al, 2012). Several animal studies have shown that arecoline administered by oral gavage to male mice induced lung adenocarcinoma and liver hemangioma (Bhide et al, 1984; Bhide et al, 1979), and chronic oral administration of arecoline through drinking water resulted in oral squamous cell carcinoma in mice (Lin et al, 2015b). However, arecoline was found not mitogenic to oral mucosal fibroblasts, and it causes cell cycle arrest of cultured oral KB epithelial cells (Chang et al, 2001; Tsai et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The lime (calcium hydroxide) used can result in an alkaline pH, triggering ROS release and causing irritation of the oral mucosa and hyperplasia [ 55 ]. Areca nut consists of phenolic compounds, and tobacco releases various nitrosamines in the mouth that are responsible for proliferative abrasions and damage to DNA and fibroblasts [ 42 , 56 ].…”
Section: Mechanism Of Genotoxicity and Carcinogenicitymentioning
confidence: 99%
“… Initial events in the pathogenesis of mouth cancer [ 56 , 63 ]. IL-6, interleukin-6; If-α, interferon-alpha; TNF, tumor necrosis factor; TGF-β, transforming growth factor-beta.…”
Section: Figurementioning
confidence: 99%